1997
DOI: 10.1074/jbc.272.31.19464
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C Terminus in Histamine H2 Receptor Signaling, Desensitization, and Agonist-induced Internalization

Abstract: To evaluate the role of the histamine H2 receptor C terminus in signaling, desensitization, and agonist-induced internalization, canine H2 receptors with truncated C termini were generated. Wild-type (WT) and truncated receptors were tagged at their N termini with a hemagglutinin (HA) epitope and expressed in COS7 cells. Most of the C-terminal intracellular tail could be truncated (51 of 70 residues, termed T 308 mutant) without loss of functions: cAMP production, tiotidine binding, and plasma membrane targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Truncations or replacements of amino acids in the C-terminal region of the receptor revealed that Thr 315 is involved in agonistinduced internalization. Interestingly, the truncated H 2 receptor mutant that deletes Thr 315 still showed desensitization measured by the cAMP production, suggesting that internalization and desensitization are mediated by independent mechanisms (19). Similar results were shown in CHO cells stably transfected with rat H 2 receptor (20).…”
Section: Roles Of C-terminal Tails Of Histamine Receptorssupporting
confidence: 72%
See 3 more Smart Citations
“…Truncations or replacements of amino acids in the C-terminal region of the receptor revealed that Thr 315 is involved in agonistinduced internalization. Interestingly, the truncated H 2 receptor mutant that deletes Thr 315 still showed desensitization measured by the cAMP production, suggesting that internalization and desensitization are mediated by independent mechanisms (19). Similar results were shown in CHO cells stably transfected with rat H 2 receptor (20).…”
Section: Roles Of C-terminal Tails Of Histamine Receptorssupporting
confidence: 72%
“…Similar to many other GPCRs, histamine H 2 receptor is desensitized and internalized after agonist stimulation. In COS-7 cells transiently transfected with canine histamine H 2 receptor cDNA, the amount of receptors on the cell surface decreased by approximately 30% after the treatment with 10 −5 M histamine, while total amount of receptor measured by [ 3 H]tiotidine binding did not change, suggesting the internalization of the receptors from the cell surface (19). Truncations or replacements of amino acids in the C-terminal region of the receptor revealed that Thr 315 is involved in agonistinduced internalization.…”
Section: Roles Of C-terminal Tails Of Histamine Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of this entire C-terminal tail in the histamine H2 receptor demonstrated a potential role in determining cell surface expression 130 while in the angiotensin II and the Bradykinin B2 receptors, C-terminal truncations did not affect cell surface expression but compromised the internalisation of each receptor 131,132 . The C-terminal tail has also been implicated in agonist-induced receptor phosphorylation in GPCRs such as the delta opioid receptor and the α1B-Adrenergic receptor 133,134 and may also function in agonist induced receptor desensitisation as shown for the α1B-Adrenergic receptor 133 .…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%